Alteration in hematological and biochemical parameters following the long-term consumption of Zataria multiflora essential oil in patients infected with liver hydatid disease - Arash Jafari (Shiraz University of Medical Sciences, 2020)
Abstract Background: Zataria multiflora Boiss is a well-known medicinal plant and its’ essential oil (EO) is traditionally used for treatment of respiratory and digestive disorders and/or bacterial, viral, fungal, and parasitic infections. Objective: This study was undertaken to evaluate the effect of long-term consumption of Z. multiflora EO on hematological and biochemical parameters in patients infected with liver hydatid disease. Materials and Methods: Fifteen patients were administered orally with Z. multiflora EO (60 mg daily) for six months. Hematological and biochemical analysis were performed on the blood samples of patients before the start of treatment and after completion of the treatment course. In hematological analysis, WBC, RBC, Hb, hematocrit, MCV, MCH, MCHC and platelets were measured. In biochemical analysis, FBS, BUN, creatinine, cholesterol, triglycerides, HDL, LDL, Na, K, Cl, AST, ALT, and ALK were assessed. Results: No apparent changes were observed in the values of hematological parameters of the patients after treatment. No significant changes also occurred in the values of FBS, BUN, creatinine, cholesterol, triglycerides, HDL, LDL, Na, and K. The mean values of AST, ALT and ALK enzymes decreased significantly after treatment (P ˂ 0.05). No adverse clinical event was noticed in the patients during the course of study. Conclusions: Long-term consumption of Z. multiflora EO induced no adverse effect on the hematological and biochemical parameters of patients infected with liver hydatid disease. Since Z. multiflora EO reduced the level of liver transaminases (AST, ALT and ALK), this herbal product may be considered as a hepatoprotective agent in human beings.